THE EFFECT OF CHANGES IN THE MAIN CHARACTER’S PERSONALITY TOWARDS SOCIAL SETTING IN LOIS LOWRY’S THE GIVER - Khairulsyah S; Ni Made Widisanti S; Tetty Yukesti (Universitas Pakuan, 2021)
The title of this research is